Sekuritasasi dan Upaya Peningkatan Perlindungan Terhadap Tenaga Kerja Indonesia di Malaysia - Hadi, Syamsul (UI Scholars Hub, 2008)
This article discuss about Indonesian worker in Malaysia, with point of view Malaysian and Indonesian government perspective in handling Indonesian illegal workers. In science context, problem about immigrant workers flipped away an issue about human security that have been one of the most important thing in international relations.